INTRUSION ALARM SYSTEM BASED ON RADIO FREQUENCY TECHNOLOGY, GPS, GSM AND DIJIKSTRAT ALGORITHM FOR NOTIFICATION TRIANGULATION - Gihonia Abraham, Senghor; MATENDO MAKENGO, Rostin; MASAKUNA Jordan, Félicien (International journal of information system and computer science, 2023)
In today's world, cars are important products that are essential to life. But when it comes to vehicle security, it's hard to start. "Vehicle theft is on the rise. Most stolen vehicles are exported abroad. The aim of this research is to develop a remote sensing notification module. In the event of a break-in, the driver is notified by SMS using GSM technology, uses GPS to track the location of the vehicle and trace the route, maps the location and uses the DIJIKSTRAT algorithm to find the nearest send a notification to the police station. The module also incorporates a prediction system for suspicious events associated with an infrared sensor. The overall idea of this research is to use large amounts of information and suspicious movements to develop a scientific model for intrusion detection. When a person approaches a parked vehicle, infrared sensors detect and compare suspicious movements in the knowledge base to detect possible intrusions. This paper proposes an anti-theft system to help car owners avoid theft and locate their car after it has been stolen. The materials referred to in this project are also actually designed.